Development of an enzyme-linked immunosorbent assay for studying Vibrio cholerae cell surface antigens. - Cryz, S J (1982)
An enzyme-linked immunosorbent assay for the measurement of antibodies directed against cell surface antigens of Vibrio cholerae (CSA ELISA) was developed. NaN3-killed whole cells of V. cholerae, adsorbed to polystyrene tubes, were used as immobilized antigens. The assay was capable of detecting antibodies directed against lipopolysaccharide and non-lipopolysaccharide surface antigens. In addition, the CSA ELISA was capable of detecting non-vibriocidal antibody. An antiserum raised in rabbits by immunization with live V. cholerae 1418 (Ogawa, El Tor) was capable of reacting with various heterologous strains of V. cholerae used as immobilized antigens. Therefore, common antigens shared by V. cholerae strains could be detected by using the CSA ELISA.